Motivation in second language teaching: theoretical and practical approach in the field of the integrated CLIL approach - Ferrando, Ernesto (2023)
The purpose of the paper is to review current theories on motivation in second language teaching from the contributions of general psychology to the field of didactics, as well as from theoretical assumptions about foreign language learning, with special attention to the CLIL approach. The importance of the study is based on the need for teachers to acquire the knowledge involved in motivation, both from the point of view of their own performance, including teaching materials, and that of their students. The methodology is based on theories on the study of motivation from the psychological perspective in relation to didactics, and the article concludes that there are a number of strategies that can help to create the necessary motivation in the classroom during the language learning process, these become practical guides for teachers in the teaching of second languages.